Greenhouse Monitoring Robot - M Vijayalakshmi; A. Sri Chandraja Reddy; CH. Sreeja; K. Chandana Lakshmi; P. Sirisha (International Journal of Robotics and Automation in Mechanics, 2023)
In the realm of agriculture, where sustainable food production is paramount, the Greenhouse Monitoring Robot emerges as a game-changing project. Greenhouse farming, with its year-round cultivation and resource efficiency, relies on precise environmental control, notably temperature and humidity. This paper focuses on the successful implementation of an autonomous Line-Following Robot equipped with sensors like the DHT11 to ensure an ideal greenhouse environment. This innovative solution has enabled the accurate recording of temperature and humidity values, facilitating comprehensive greenhouse monitoring and management for optimal crop growth and resource utilization.
Keywords: Autonomous moment; Dynamic system; Green house; Humidity monitoring; Line follower robot; Temperature monitoring